ESR1 Mutations Affect Anti-proliferative Responses to Tamoxifen through Enhanced Cross-Talk with IGF Signaling - Gelsomino, Luca (Breast Cancer Res Treat, 2016)
It is now generally accepted that estrogen receptor (ESR1) mutations occur frequently in metastatic breast cancers, however we do not yet know how to best treat these patients. We have modeled the three most frequent hormone binding ESR1 (HBD-ESR1) mutations (Y537N, Y537S, and D538G) using stable lentiviral transduction in human breast cancer cell lines. Effects on growth were examined in response to hormonal and targeted agents, and mutation-specific changes were studied using microarray and western blot analysis. We determined that the HBD-ESR1 mutations alter anti-proliferative effects to tamoxifen (Tam), due to cell-intrinsic changes in activation of the insulin-like growth factor receptor (IGF1R) signaling pathway and levels of PIK3R1/PIK3R3. The selective estrogen receptor degrader, fulvestrant, significantly reduced the anchorage-independent growth of ESR1 mutant-expressing cells, while combination treatments with the mTOR inhibitor everolimus, or an inhibitor blocking IGF1R and the insulin receptor significantly enhanced anti-proliferative responses. Using digital drop (dd) PCR we identified mutations at high frequencies ranging from 12% for Y537N, 5% for Y537S, and 2% for D538G in archived primary breast tumors from women treated with adjuvant mono-tamoxifen therapy. The HBD-ESR1 mutations were not associated with recurrence-free or overall survival in response in this patient cohort, and suggest that knowledge of other cell-intrinsic factors in combination with ESR1 mutation status will be needed determine anti-proliferative responses to Tam.